Reducing the Social Cost of Federal Crop Insurance: A Role for Government Hedging with Weather Derivatives - 정원호 (한국농촌경제연구원, 2013)
Previous studies have shown that weather derivatives are an effective means of hedging agricultural production risk. Yet, it is still unclear what role weather derivatives will play in agriculture as a risk management tool as compared with existing crop insurance programs which depend highly on government subsidies. This study compares the hedging cost and effectiveness of weather options and crop insurance for soybean in southern Minnesota. Our results show that the hedging effectiveness of weather options is limited at the farm level while the effectiveness increases as the level of aggregation increases. Thus, individual farmers will continue to prefer the federal crop insurance program to weather derivatives for their production risk management. However, the US government as an insurer, which currently does not hedge its risk exposures taken from farmers in the federal crop insurance program, could reduce the implied social cost in the form of un-hedged risk exposure by use of the weather options in the financial market.